The Incidence of Sick Building Syndrome and Its Causes on Employees at the Governor’s Office of West Sulawesi Province - Ridhayani Adiningsih; Miftah Chairani Hairuddin (Universitas Airlangga, 2021)
Introduction: Indoor air quality greatly affects human health because almost 90% of human life is indoors. Some symptoms that are often felt by employees in a building with Sick Building Syndrome (SBS) are fatigue; headaches; symptoms of eye, nose and throat irritation; skin irritation; dry cough, increased irritability and difficulty in concentration; nausea; drowsiness; and hypersensitivity to odor. This research aims to determine the relationship of air quality in space to the incidence of Sick Building Syndrome. Methods: This research was an analytic survey research with cross sectional approach. The samples in this study were employees who were in the Building D of the Provincial Governor's Office, West Sulawesi totalling 82 people. This research was carried out by measuring indoor air quality and giving questionnaires to find out the SBS events. Results: The results of room temperature measurements ranged from 26.14 - 41.46°C, humidity measurement was ≥ 60%, light intensity was ≤ 100 lux, the chemical quality of CO in the air was ≤ 29 mg/m3, CO2 levelin the air was ≤ 1000 ppm, and dust level was ≥ 0.15 mg/m3. Besides, there was a significant relationship between air temperature and dust levels on the incidence of Sick Building Syndrome (SBS), with p value of 0.006. Conclusion: It can be concluded that factors that influenced the occurrence of SBS were air temperature and dust concentration in the room.Keywords: indoor air quality, office, sick building syndrome